Analysis of clinical drug use and construction of pharmacy service model for children with Kawasaki disease based on integration concept - Huashen He; Yingyao Luo; Binghong Yu; Yingqiang Lai; Jinkun Zheng; Junfeng Ban (KeAi Communications Co., Ltd., 2023)
Objective: This study aimed to summarize and share the experience of clinical pharmacists in the clinical treatment of children with Kawasaki disease based on the "integration" concept. Methods: Clinical pharmacists were actively involved in the treatment of children with Kawasaki disease by providing rational drug selection, adjustment advice, and pharmacological monitoring services. Hence, we proposed a pharmacy service model for children with Kawasaki disease based on the "integration" concept. Results: The pharmacy service model based on the "integration" concept was initially developed by applying integration perception to clinical medication practice, allowing the clinical pharmacist to assist the clinician in controlling the infection in children, and children were discharged from the hospital in good condition. Conclusion: Clinical pharmacists should initiate cooperation with the treatment team in clinical work and use their professional advantages to ensure that sick children meet the expectations in the medication treatment process to play a crucial role in clinical pharmacy services.